2021
DOI: 10.1111/tri.14121
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analyses of regional perfusion in donation after circulatory death solid organ transplantation

Abstract: In donation after circulatory death (DCD), (thoraco)abdominal regional perfusion (RP) restores circulation to a region of the body following death declaration. We systematically reviewed outcomes of solid organ transplantation after RP by searching PubMed, Embase, and Cochrane libraries. Eighty-eight articles reporting on outcomes of liver, kidney, pancreas, heart, and lung transplants or donor/organ utilization were identified. Meta-analyses were conducted when possible. Methodological quality was assessed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 131 publications
(51 reference statements)
1
78
0
1
Order By: Relevance
“…This technique can potentially improve post‐transplant outcomes by reversing ischemia‐damaged tissue, limiting the cold ischemia period and allows clinicians to validate organs prior to recovery 1,9 . A‐NRP reduces post‐transplant biliary complications in cDCD livers, 10,11 and international multicenter studies have shown that liver and kidneys obtained with A‐NRP versus the RR technique improves graft survival 10,12,13 . A‐NRP is now routinely used in cDCDs in France, Italy, Spain, and the UK, and is being piloted in Belgium, the Netherlands, Norway, and Switzerland 10,12‐15 …”
Section: Introductionmentioning
confidence: 99%
“…This technique can potentially improve post‐transplant outcomes by reversing ischemia‐damaged tissue, limiting the cold ischemia period and allows clinicians to validate organs prior to recovery 1,9 . A‐NRP reduces post‐transplant biliary complications in cDCD livers, 10,11 and international multicenter studies have shown that liver and kidneys obtained with A‐NRP versus the RR technique improves graft survival 10,12,13 . A‐NRP is now routinely used in cDCDs in France, Italy, Spain, and the UK, and is being piloted in Belgium, the Netherlands, Norway, and Switzerland 10,12‐15 …”
Section: Introductionmentioning
confidence: 99%
“…In their recent consensus statement, 9 the European Society for Organ Transplantation (ESOT) recommends to use normothermic regional perfusion (NRP) of the abdomen cDCD procedures, rather than in-situ cooling and cold static storage, if ethical, technical and logistical requirements are met, to improve recipients outcome, potentially preventing some post-transplant complications. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…Data supporting the use of NRP in cDCD is provided by observational studies, primarily arising from Europe. A recent systematic review and meta‐analysis determined the use of postmortem NRP in cDCD liver transplantation was associated with a 71% reduction in the development of any form of biliary stricture(s) (relative risk [RR] 0.29, 95% confidence interval [CI] 0.15–0.57) and 85% reduction in ischemic‐type biliary lesions (ITBL) (RR 0.15, 95% CI 0.105–0.45) relative to SRR 37 . Decreased risk of liver graft loss (adjusted hazard ratio [HR] 0.39, 95% CI 0.20–0.78) has also been described in the context of a propensity‐adjusted multicenter study 38 .…”
Section: In Situ Normothermic Regional Perfusionmentioning
confidence: 99%